Swansoft Simulator Video Tutorial as Digital Media for Basic Computer Numerical Control Learning - Amelia Dini Wulandari; Marsono; Puteri Ardista Nursisda Mawangi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Basic CNC learning in vocational high schools faces challenges including limited practical facilities and low student procedural understanding of CNC machine programming. This study aims to analyze the effect of Swansoft CNC Simulator-based video tutorial media on improving student cognitive learning outcomes. The research employed a one-group pretest-posttest quasi-experimental design. The research subjects consisted of 10 students in grade XI of the Machining Engineering program at SMK Muhammadiyah 1 Malang City, selected through purposive sampling. Data were collected through cognitive tests (30 multiple-choice items based on Bloom’s Revised Taxonomy covering C1–C5 levels) and analyzed using paired samples t-test. The results showed a statistically significant improvement in student learning outcomes (t(9) = −2.674, p = 0.025, Cohen’s d = 0.99), with a mean score increase from 73.60 (SD = 7.20) on the pretest to 81.30 (SD = 8.25) on the posttest, yielding a mean normalized gain (N-Gain) of 0.29 (low-moderate category). These findings indicate that simulation-based video tutorial media integrating visual and auditory channels effectively enhances conceptual understanding and programming accuracy in CNC machining. This study concludes that Swansoft CNC Simulator-based video tutorial media is effective as an instructional alternative for Basic CNC courses at the vocational secondary school level.